Developing the health workforce for universal health coverage - Cometto, Giorgio (2020)
Optimizing the management of the health workforce is necessary for the progressive realization of universal health coverage. Here we discuss the six main action fields in health workforce management as identified by the Human Resources for Health Action Framework: leadership; finance; policy; education; partnership; and human resources management systems. We also identify and describe examples of effective practices in the development of the health workforce, highlighting the breadth of issues that policy-makers and planners should consider. Achieving success in these action fields is not possible by pursuing them in isolation. Rather, they are interlinked functions that depend on a strong capacity for effective stewardship of health workforce policy. This stewardship capacity can be best understood as a pyramid of tools and factors that encompass the individual, organizational, institutional and health system levels, with each level depending on capacity at the level below and enabling actions at the level above. We focus on action fields covered by the organizational or system-wide levels that relate to health workforce development. We consider that an analysis of the policy and governance environment and of mechanisms for health workforce policy development and implementation is required, and should guide the identification of the most relevant and appropriate levels and interventions to strengthen the capacity of health workforce stewardship and leadership. Although these action fields are relevant in all countries, there are no best practices that can simply be replicated across countries and each country must design its own responses to the challenges raised by these fields.